Features of the implementation of the concept of «mental health» in the field of adaptive physical culture in the republic of tatarstan - Frolova E.V.; Parfenova L.A.; Burtseva E.V. (Theory and Practice of Physical Culture, 2025)
The purpose of the study. To determine the specifics of the implementation of the "Mental Health" Concept in the field of adaptive physical culture (AFC), taking into account the target groups. Methodology and organization of the study. The analysis of the current state has been carried out, the place and role of adaptive physical culture in the system of comprehensive support for people with mental disabilities in the Republic of Tatarstan has been established, the target groups of the Concept in the field of AFC have been identified. A sociological study aimed at identifying interest and motivation (preferences) in sports rehabilitation and physical education classes, taking into account their requests, opportunities and educational needs. The results of the study and conclusions. The Tatarstan Republican regional branch of the All-Russian Public Charity Organization "Special Olympics of Russia" and the regional branch of the All-Russian Federation of Sports for Persons with Intellectual Disabilities are actively developing adaptive physical education and sports for persons with ASD and DMN in the Republic of Tatarstan. Social and sports work is carried out jointly with the Department of Adaptive Physical Culture of the Volga State University of Physical Culture, Sports and Tourism. The Tatarstan branch of the Special Olympics unites more than 7,000 participants, including athletes and volunteers, regular trainings and classes on adaptive sports technologies are held. The organization’s partners include more than 100 institutions, including correctional schools, rehabilitation centers, sports federations, and charitable foundations. Great importance is given to the preparation of athletes for participation in All-Russian competitions. The University provides classes for 210 people, including children with ASD, in various sports. Correctional and developmental classes for preschoolers and young people with disabilities are organized, modern physical education and wellness technologies are used. The positive experience of cooperation was included in the AFC Concept. Activities are being implemented in various areas, including professional development and the integration of Special Olympics programs into educational institutions. Systematic work is underway with families of children with mental disabilities, joint activities and consultations are conducted.